Contribution of neighbourhood socioeconomic status and physical activity resources to physical activity among women. Issue 10 (14th September 2007) - Lee, Rebecca E; Cubbin, Catherine; Winkleby, Marilyn
Abstract : Introduction: Residence in a deprived neighbourhood is associated with lower rates of physical activity. Little is known about the manifestation of deprivation that mediates this relationship. This study aimed to investigate whether access to physical activity resources mediated the relationship between neighbourhood socioeconomic status and physical activity among women. Method: Individual data from women participating in the Stanford Heart Disease Prevention Program (1979–90) were linked to census and archival data from existing records. Multilevel regression models were examined for energy expenditure and moderate and vigorous physical activity as reported in physical activity recalls. Results: After accounting for individual-level socioeconomic status, women who lived in lower-socioeconomic status neighbourhoods reported greater energy expenditure, but undertook less moderate physical activity, than women in moderate-socioeconomic status neighbourhoods. In contrast, women living in higher-socioeconomic status neighbourhoods reported more vigorous physical activity than women in moderate-socioeconomic status neighbourhoods. Although availability of physical activity resources did not appear to mediate any neighbourhood socioeconomic status associations, several significant interactions emerged, suggesting that women with low income or who live in lower-socioeconomic status neighbourhoods may differentially benefit from greater physical activity resource availability. Discussion: Although we found expected relationships between residence in a lower-socioeconomic status neighbourhood and undertaking less moderate or vigorous physical activity among women, we also found that these same women reported greater overall energy expenditure, perhaps as a result of greater work or travel demands. Greater availability of physical activity resources nearby appears to differentially benefit women living in lower-socioeconomic status neighbourhoods and low-income women, having implications for policy-making and planning.